2020
DOI: 10.1038/s41598-020-70022-0
|View full text |Cite
|
Sign up to set email alerts
|

Optimisation of Tet-On inducible systems for Sleeping Beauty-based chimeric antigen receptor (CAR) applications

Abstract: Regulated expression of genetic elements that either encode polypeptides or various types of functional RNA is a fundamental goal for gene therapy. Inducible expression may be preferred over constitutive promoters to allow clinician-based control of gene expression. Existing Tet-On systems represent one of the tightest rheostats for control of gene expression in mammals. However, basal expression in absence of tetracycline compromises the widespread application of Tet-controlled systems in gene therapy. We dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 47 publications
2
24
0
Order By: Relevance
“…The target gene expression can be detected within 30 min after nontoxic Dox added and maximal expression levels can be higher than expression levels obtained from the CMV promoter 42 . Therefore, the Tet‐on system has been applied to develop a tissue‐specific delivery system on cell therapy and generate controllable transgene expression systems to produce animal models of disease 43–45 . Herein, we first generated inducible cell lines to quantify ZIKV C–C interaction based on the SLCA and Tet‐on system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The target gene expression can be detected within 30 min after nontoxic Dox added and maximal expression levels can be higher than expression levels obtained from the CMV promoter 42 . Therefore, the Tet‐on system has been applied to develop a tissue‐specific delivery system on cell therapy and generate controllable transgene expression systems to produce animal models of disease 43–45 . Herein, we first generated inducible cell lines to quantify ZIKV C–C interaction based on the SLCA and Tet‐on system.…”
Section: Discussionmentioning
confidence: 99%
“…By using of this system, synthetic peptides Pep.15-24 and Pep. [44][45][46][47][48][49][50][51][52][53][54][55][56][57][58] were identified to inhibit ZIKV C-C interaction. This well-established inducible assay system targeting ZIKV capsid interaction can be applied for future discovery of anti-ZIKV drugs.…”
mentioning
confidence: 99%
“…Recently, our group developed a Tet‐On system for CAR T cell applications. We showed that introducing a G72V mutation in rtTA (G72V‐rtTA) described previously for yeast, 105 significantly enhanced the Tet‐On system function in large gene cassettes containing a CAR 106 . Such a system might be beneficial when the expression of a miRNA needs to be regulated during T cell differentiation.…”
Section: Introductionmentioning
confidence: 94%
“…We showed that introducing a G72V mutation in rtTA (G72V-rtTA) described previously for yeast, 105 significantly enhanced the Tet-On system function in large gene cassettes containing a CAR. 106 Such a system might be beneficial when the expression of a miRNA needs to be regulated during T cell differentiation. For instance, let-7 has an increased expression within T N and T M cells whilst is downregulated in T EFF cells.…”
Section: Strategies To Overexpress Mirna In Car T Cellsmentioning
confidence: 99%
“…A solution to the basal activity of the Tet-on system has also been proposed in the CAR context, by introducing the G72V mutation in the TetR region. This resulted in a 40-fold reduction in Dox-independent activation [ 54 ]. An interesting study that proposed the possibility of additional control coupled the activation of the Tet system, not only to Tc but also to blue light similar to the Cre system [ 55 ].…”
Section: Receptor Switchesmentioning
confidence: 99%